Initiation-Response-Feedback (IRF) Pattern of Sinclair and Coulthard Model In English Classroom Interaction - Uswatun Hasanah; Neni Afrida Sari; Rahmad Husein (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The study investigated the implementation of the Initiation-Response-Feedback (IRF) pattern of Coulthard and Sinclair Model in sixth-grade classroom interactions. It focused on its impact on student engagement and learning outcomes. Conducted with an English teacher and 23 students, the research utilized video recordings to analyze discourse patterns during lessons. Findings reveal that the IRF model facilitated communication by structuring interactions where teachers initiate questions, students respond, and teachers provide feedback. However, the analysis indicated that while students actively participate, their responses often consist of repetition rather than demonstrating comprehension of the material. Teacher feedback plays a crucial role in reinforcing learning, yet it also highlighted areas needing improvement in fostering deeper understanding. The study emphasizes the importance of teacher-student dialogue in creating an interactive learning environment and suggests that educators should encourage critical thinking and comprehension alongside participation. By identifying best practices within the IRF framework, this research contributes to enhancing classroom dynamics in early secondary education settings.